Developmental Biology of the Aquatic Beetle Berosus alternans Brullé (Coleoptera: Hydrophilidae) in the Laboratory - Fernandez, Liliana Alicia (2005)
A stage-specific vertical life table of the aquatic beetle Berosus alternans Brullé was constructed based on a laboratory study. Embryonic development time was estimated as 3.5 days. Eggs hatched between the 4th and 14th days after being laid. Females constructed, on average, 2.46 eggs cases per day during 84 consecutive days. The first oviposition occurred on the 6th day after mating, extending until the 84th days. The mean durations of instars and stages were: eggs, 6.12; L1, 4.93; L2, 5.13; L3, 11.17; pre-pupa, 109.12 and pupa, 7.31 days. Preadult development time was completed in 127.6 days for males, and in 154.4 days for females. When we tested mean duration by developmental stage, pre-pupa was significantly longer for females than for males (P<0.01). Relative mortality was highest in the third instar, followed by pupal stage.